An Empirical Analysis of Ergonomic Gaming Peripherals Improving Gaming Performance - Gede Indra Raditya Martha; I Gede Bintang Arya Budaya; Dedy Panji Agustino; I Gede Harsemadi; I Made Suandana Astika Pande (Journal of Games, Game Art, and Gamification, 2022)
The gaming industry is a huge industry that is based on creativity and the use of media as well as the latest technology. According to the Entertainment Software Association (ESA) in 2021 more than 227 million Americans playing video games, and 75% of USA households have at least one person who plays games and has a gaming device on their home. The facts mentioned before makes this industry very profitable to enter. In hardware aspect, some company innovates to make a specific device which is used special for gaming needs. This gaming device main selling points is high specification and ergonomics factor for improving gaming performance. Despite the successful sale of this product, many people still doubt the effectiveness of gaming peripheral products to improve gaming performance and whether the higher specification of gaming peripheral can truly improve player performance during gameplay. The Study is based on the effectiveness of peripheral on human perception sensor that can be used in the implementation of ergonomic science / physical engineering or HCI (Human Computer Interaction), namely vision, hearing, and touch. In that case, with qualitative research method (direct observation, interview & simulation) this study found as the result, that was true the gaming peripherals are able to improve the performance of the user, but not for all types of users. The competitive gamer who has high gameplay hours can benefit the most and use maximum potential performance of gaming peripherals.